Effects of Covid-19 Pandemic on Food Insecurity Perception in Chilean Households [Inseguridad Alimentaria y Hábitos Alimentarios Durante la Pandemia de Covid-19 en Hogares Chilenos] - Pizarro-Quevedo, T (Sociedad Medica de Santiago, 2021)
Background: The coronavirus 2 pandemic (COVID-19) has caused intense changes in lifestyles, feeding, and nutrition habits. Aim: To analyze food insecurity and eating habits during the period of quarantine in a group of Chilean individuals. Material and Methods: An online survey was conducted in 2,767 households with questions about the sociodemographic composition of the household, household food purchasing habits in the quarantine period for COVID-19, and perception of food insecurity. Results: More than 60% of households (p < 0.01) were worried about not having enough food, especially when children under 18 years of age lived in them. This perception increased in urban households (p < 0.01) and those located in the Central-Southern and Southern regions (p < 0.01). During the pandemic, the consumption of healthy products such as milk increased in 50% of households, legumes in 72%, eggs in 79%, fruits in 54%, vegetables in 67% and water in 81%. There was also a lower consumption of unhealthy and ultra-processed foods such as hot-dogs in 90% of households, sausages in 73%, sugary drinks in 79% and ice cream in 83%. Conclusions: The COVID-19 pandemic in Chile increased the perception of food insecurity in households with vulnerable conditions. However, the consumption of healthier foods increased. © 2021 Sociedad Medica de Santiago. All rights reserved.